OUTPATIENT PATIENT SATISFACTION WITH MEDICATION INFORMATION SERVICES AT X PRIMARY INPATIENT CLINIC BASED ON MINISTER OF HEALTH REGULATION NO. 34 OF 2021 - Putri Ade Fitriani; Tisa Amalia; Ayu Izzatin Haifa (Politeknik META Industri Cikarang, 2026)
Background Drug information services are a critical component of pharmaceutical care, ensuring patient safety and therapeutic adherence. However, suboptimal delivery of drug information remains a challenge in primary health facilities, potentially leading to patient non-compliance and increased risk of adverse drug reactions. Purpose This study aims to determine the level of outpatient satisfaction with drug information services at Klinik Pratama Rawat Inap X based on Regulation of the Minister of Health Number 34 of 2021 concerning Pharmaceutical Service Standards in Clinics. Methodology A descriptive quantitative method with a cross-sectional approach was employed. Data were collected through a validated nine-item questionnaire distributed to 98 outpatients selected using the Slovin formula. Data analysis used Likert scale (1-5) with percentage calculation and categorized into five satisfaction levels.. Findings The overall satisfaction rate was 69% (satisfied category). The highest score was for drug benefit information (85%, very satisfied), while the lowest was for drug storage information (69%, satisfied). Three mandatory information items, side effects (70%), precautions (70%), and storage (69%), were at the lower threshold of the satisfied category. The staff-to-patient ratio (1:85) exceeded the recommended standard (1:50), contributing to incomplete information delivery. Implications This study recommends strengthening regulatory compliance, increasing pharmaceutical staff capacity, and improving supervision of drug information services in primary health facilities to enhance patient satisfaction and therapeutic outcomes. Originality This research provides a comprehensive evaluation of outpatient satisfaction with drug information services specifically in a primary care clinic setting, using a multidimensional assessment aligned with national regulatory standards.